Book review: Howell, Jude, editor. 2012: Global Matters for Non-governmental Public Action. (April 2014) - Fontefrancesco, Michele
Howell, Jude, editor. 2012: Global Matters for Non-governmental Public Action . Basingstoke: Palgrave Macmillan. 24 pp. £ 65.00 hardback. ISBN: 9780230290358.